2021
DOI: 10.1017/jog.2021.122
|View full text |Cite
|
Sign up to set email alerts
|

Using bed-roughness signatures to characterise glacial landform assemblages beneath palaeo-ice sheets

Abstract: Palaeo-glacial landforms can give insights into bed roughness that currently cannot be captured underneath contemporary-ice streams. A few studies have measured bed roughness of palaeo-ice streams but the bed roughness of specific landform assemblages has not been assessed. If glacial landform assemblages have a characteristic bed-roughness signature, this could potentially be used to constrain where certain landform assemblages exist underneath contemporary-ice sheets. To test this, bed roughness was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
(161 reference statements)
0
3
0
Order By: Relevance
“…According to our results, these gradient changes limit the propagation of the thinning from the terminus. Previous research has shown that bed roughness is important in controlling glacier dynamics (Falcini et al, 2022) and ice flow resistance (Hoffman et al, 2022). Roughness is generally found to be associated with the presence of hills, valleys, and bumps under the ice.…”
Section: Empirical Limit Based On Kinematic Wave Theory and Its Relat...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to our results, these gradient changes limit the propagation of the thinning from the terminus. Previous research has shown that bed roughness is important in controlling glacier dynamics (Falcini et al, 2022) and ice flow resistance (Hoffman et al, 2022). Roughness is generally found to be associated with the presence of hills, valleys, and bumps under the ice.…”
Section: Empirical Limit Based On Kinematic Wave Theory and Its Relat...mentioning
confidence: 99%
“…This highlights the importance of combining bed geometric analysis with lithological variability. On the other hand, ice flow can smooth the bed and consequently generate substantial changes in glacier dynamics (Falcini et al, 2022).…”
Section: Limitations Of Our Analysis and Future Workmentioning
confidence: 99%
“…To address these uncertainties, many studies have sought to use landscapes left behind by former ice sheets to inform model-parameter choices [9][10][11]. High-resolution surveys of these deglaciated landscapes clearly depict substrates whose roughness and deformability vary considerably over the several-km scale that previous work has shown is crucial to determine rates of ice flow and glacial retreat under climate forcing [12][13][14][15]. Across Antarctica, limited geological exposures in exposed, subaerial mountain ranges and around the margins offer some insights into the properties of the buried bed [16], but the majority of what is known about the ice-bed interface across the Antarctic interior comes from geophysical surveys [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%